Case Law and the Principle of Freedom of Judicial Power in the Law Finding by Judges - Widowati, Christiani (Fakultas Hukum Universitas Airlangga, 2024)
Case law is a complementary source of law for law finding carried out by judges. The tendency of judges to refer to case law is intended so that judges’ decisions have a predictable nature and eliminate disparities in judges’ decisions. On the other hand, the principle of freedom of judicial power is a condition sine qua non for law enforcement and justice through judges’ law finding as the implementation of judicial power. The position of case law is a manifestation of legal certainty for judges’ decisions and a denial of judges’ freedom when deciding cases. This study aims to provide an in-depth analysis of the position of case law as a source of law for judges to use in law finding. The statute approach method by examining laws and regulations and judges’ decisions related to the focus of this study, then complemented by a conceptual approach by moving on to legal principles that can be found in laws and regulations, judges’ decisions, and legal doctrines, it is understood that judges’ law finding are essentially aimed at upholding justice so that judges are not fixated on the provisions of laws and regulations or case law. Justice is the starting point for judges’ law finding; then judges construct legal norms that are stated into their decisions.